Can Ownership Structure, Capital Structure, and Company Value Determine a Company's Dividend Policy? - Asrini Asrini; Musnaini Musnaini (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Backgrounds: Inconsistency or inaccuracy in dividend payments can undermine investor confidence in managers. Companies that implement a dividend policy are those with adequate financial performance, performance prospects, and capital structure. Objectives: This study was conducted to determine the effect of managerial ownership, institutional ownership, capital structure and firm value on dividend policy as well as the moderating effect of firm value on the relationship between managerial ownership, institutional ownership and capital structure with dividend policy. Method: Based on quantitative research methods with purposive sampling techniques, 10 companies in the manufacturing sector of the consumer goods industry sub-sector were obtained on the IDX in the 2018-2022 period. Results: The results showed that there is an influence between institutional ownership, capital structure and firm value on dividend policy, while managerial ownership has not been able to influence dividend policy, and firm value can moderate the relationship between institutional ownership and capital structure on dividend policy Conclusion: Companies should maintain their management performance to attract investors and consistently distribute dividends to their shareholders. Furthermore, companies must also determine an appropriate dividend policy, as it will impact the well-being of the company and its shareholders. Furthermore, investors should consider the percentage of institutional share ownership before investing, as this study demonstrates that higher institutional ownership leads to higher dividends. Finally, academics should conduct similar research with different subjects to support previous research.